Preliminary screening of biomarkers in HAPE based on quasi-targeted metabolomics - Lin, Xue; Dai, Chongyang; Chen, Zhi; Zhang, Tongzuo; Pu, Xiaoyan (Frontiers in Physiology, 2023)
High altitude pulmonary edema (HAPE) is a serious threat to the physical and mental health of people who quickly enter high plateaus, deserves more attention and in-depth research. In our study, through the detection of various physiological indexes and other phenotypes in a HAPE rat model, the HAPE group showed a significant decrease in oxygen partial pressure and oxygen saturation, and a significant increase in pulmonary artery pressure and lung tissue water content. The lung histomorphology showed characteristics such as pulmonary interstitial thickening and inflammatory cell infiltration. We applied quasi-targeted metabolomics to compare and analyze the components of metabolites in arterial–veinous blood in control rats and HAPE rats. Using kyoto Encyclopedia of Genes Genomes (KEGG) enrichment analysis and two machine algorithms, we speculate that after hypoxic stress and comparing arterial blood and venous blood products in rats, the metabolites were richer, indicating that normal physiological activities, such as metabolism and pulmonary circulationhad a greater impact after hypoxic stress; D-mannoseDOWN, oxidized glutathioneDOWN, glutathione disulfideDOWN, and dehydrocholic acidDOWN in arterial blood play key roles in predicting the occurrence of HAPE; in venous blood, L-leucineDOWN, L-thyroxineDOWN, and cis-4-hydroxy- D-prolineDOWN may have key roles, which can be considered biomarkers of HAPE. This result provides a new perspective for the further diagnosis and treatment of plateau disease and lays a strong foundation for further research.